Systematic Review of Comparative Patient Reported Outcomes and Health-Related Quality of Life After Management of Localized Renal Masses or Renal Cell Carcinomas - Laura Sandbergen; Muhammad Imran Omar; Lavin Othman; Faridi van Etten-Jamaludin; Mustafa Soytas; Jean J. de la Rosette; M. Pilar Laguna (Société Internationale d’Urologie Journal)
ObjectiveTo perform a systematic review assessing the impact of the different management options on health-related quality of life (HRQoL) of patients with localized renal masses or renal cell carcinomas (LRM/LRCC). Materials and MethodsSearches covering PubMed, Embase (Ovid), CENTRAL, PsycINFO (Ovid), CINAHL (EBSCO), and Cochrane Central Register of Controlled Trials (CENTRAL) databases was conducted for papers published up to 25 April 2021. Methods as per Cochrane Handbook were followed. “Modality” of treatment included radical nephrectomy (RN), nephron-sparing surgery (NSS), thermal ablation (TA), and active surveillance (AS). “Approach” was categorized as open incision and minimally invasive surgery (MIS). Risk of bias was assessed by ROBINS-I and Cochrane RoB 2 for observational studies and randomized controlled trials, respectively and certainty of the evidence by GRADE. ResultsSixteen observational studies and 1 randomized controlled trial (2.370 patients) met inclusion criteria. Fifteen different patient reported outcome measures (PROMs) were identified. Heterogeneity prevented quantitative analysis.Generic HRQoL decreases after RN and NSS, recovers within 6 to 12 months, and mostly overlaps with baseline values, irrespective of modality. Cancer-specific HRQoL improves faster after open-NSS than open-RN. The detrimental effect of RN may persist long-term in cross-evaluations. QoL scales significantly decrease after open surgery and MIS during the first weeks but improve faster after MIS. They are similar for both approaches at 1 year. Long-term cancer-specific QoL is similar for MIS and open procedures. Fear of recurrence is lower in older patients and affected by neither modality nor approach. ConclusionsLow quality evidence supports the use of MIS over the open approach when HRQoL is considered in the management of LRMs/LRCCs; data regarding the effect of the treatment modality of the LRM/LRCC show contradictory outcomes.